Human‐directed attachment behavior in wolves suggests standing ancestral variation for human–dog attachment bonds. Issue 9 (20th September 2022) - Hansen Wheat, Christina; Larsson, Linn; Berner, Patricia; Temrin, Hans
Abstract: Domesticated animals are generally assumed to display increased sociability toward humans compared to their wild ancestors. Dogs ( Canis familiaris ) have a remarkable ability to form social relationships with humans, including lasting attachment, a bond based on emotional dependency. Since it has been specifically suggested that the ability to form attachment with humans evolved post‐domestication in dogs, attempts to quantify attachment behavior in wolves ( Canis lupus ) have subsequently been performed. However, while these rare wolf studies do highlight the potential for wolves to express human‐directed attachment, the varied methods used and the contrasting results emphasize the need for further, standardized testing of wolves. Here, we used the standardized Strange Situation Test to investigate attachment behavior expressed in wolves and dogs hand‐raised and socialized under standardized and identical conditions up until the age of testing. We found that 23‐week‐old wolves and dogs equally discriminated between a stranger and a familiar person, and expressed similar attachment behaviors toward a familiar person. Additionally, wolves, but not dogs, expressed significantly elevated stress‐related behavior during the test, but this stress response was buffered by the presence of a familiar person. Together, our results suggest that wolves can show attachment behaviors toward humans comparable to those of dogs. Importantly, our findings demonstrate that the ability to form attachment with humans exists in relatives of the wild ancestor of dogs, thereby refuting claims that this phenotype evolved after dog domestication was initiated. Abstract : Disentangling whether specific phenotypes seen in domesticated populations have evolved via novel mutations or are in fact based in standing ancestral variation is of particular importance when we try to understand how domestication might have proceeded and how phenotypes evolve. It has been specifically been suggested that the ability to form attachment (i.e. a social bond based on emotional dependency) with humans evolved post‐domestication in dogs, yet here we show that hand‐raised wolves also express human‐directed attachment. Our findings demonstrate that the ability to form attachment with humans exists in relatives of the wild ancestor of dogs, thereby refuting claims that this phenotype evolved after dog domestication was initiated.